Псы Вавилона: [роман] / Алексей Агеев - Атеев Алексей Григорьевич (Король Ужасов, 2002)
Экземпляры: ф.12 (20191220) / Инвентарный номер: 51720 / Цена: 100.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 92 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-4